(untitled) (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study aims to analyze the effect of time management and discipline on student learning outcomes in Economics subjects at Senior High School of 9 Pekanbaru. The background of this research is the low learning outcomes of students. The method used was quantitative with a population of 437 students and a sample of 209 students, selected by proportional random sampling. Data were collected through documentation and questionnaires, and analyzed using multiple linear regression. The results showed that both time management and discipline had a positive and significant effect on learning outcomes partially and simultaneously. The significance value of each variable is <0.05 and the coefficient of determination (R²) is 0.539, indicating that 53.9% of the variation in learning outcomes is influenced by these two variables. Thus, time management and discipline play an important role in improving the learning outcomes of Economics students at Senior High School of 9 Pekanbaru.